Hypogastric artery coverage during endovascular aneurysm repair in octogenarian and younger patients. Issue 8 (August 2019) - Mazzaccaro, Daniela; Miri, Rim; Derbel, Bilel; Modafferi, Alfredo; Nano, Giovanni
Abstract : Aim: To report our experience about hypogastric artery coverage during endovascular aneurysm repair (EVAR) for aortoiliac aneurysms in patients younger than 80 years (group A) compared with octogenarian patients (group B). Methods: Data of consecutive EVAR with hypogastric artery coverage from 01/1998 to 12/2016 were retrospectively analyzed. Primary outcomes were the occurrence of ischemic colitis, type II endoleak and buttock claudication both at 30 days and in the long term. P values less than 0.05 were considered statistically significant. Results: The hypogastric artery was covered in 107 patients. Twenty-three (21.5%) were octogenarian (group B). At 30 days, one type II endoleak occurred in group B, whereas 16 patients of group A experienced buttock claudication. There were no cases of ischemic colitis. During follow-up (median 63.5 months), no cases of ischemic colitis occurred. Six new type II endoleaks were recorded (five in group B and one in group A, P  = 0.0001). Buttock claudication persisted in four patients of group A. No new cases of buttock claudication were observed. Conclusion: Unilateral hypogastric artery coverage during EVAR for aortoiliac aneurysms can be performed with an acceptable rate of postoperative complication. Postoperative buttock claudication was more frequent in younger patients, whereas a type II endoleak occurred mostly in octogenarian patients during follow-up.